Changing Patterns of Carotid Endarterectomy Between 2011 and 2017 in England: A Population-Based Cohort Study. Issue 9 (September 2019) - Johal, Amundeep S.; Loftus, Ian M.; Boyle, Jonathan R.; Naylor, A. Ross; Waton, Sam; Heikkila, Katriina; Cromwell, David A.
Abstract : Background and Purpose—: Carotid endarterectomy (CEA) reduces the risk of stroke in recently symptomatic patients and less so in asymptomatic patients. Recent evidence suggests that the number of CEAs may be declining. The aim of this study was to investigate annual patterns of CEA in asymptomatic and symptomatic patients in England from 2011 to 2017. Methods—: Data from the National Vascular Registry were used to describe (1) the number of CEA procedures in England and its 9 geographic regions from 2011 to 2017, (2) the characteristics of patients undergoing CEA, and (3) whether rates of CEA correlated with the number of vascular arterial units within each region. Annual stroke incidence for each region was derived from official population figures and the number of index stroke admissions per year. Results—: The overall number of CEAs performed in England fell from 4992 in 2011 to 3482 in 2017, a 30% decline. Among symptomatic patients, there was a 25% decline, the number of CEAs falling from 4270 to 3217. In asymptomatic patients, there were 722 CEAs performed in 2011 and 265 in 2017, a 63% decline. CEAs per 100 000 adults within all regions declined over time but the size of change varied across the regions (range, 1.7–5.5 per 100 000). The regional numbers of CEAs per year were associated with changes in the regional stroke incidence, the proportion of CEAs performed in asymptomatic patients, and the number of hospitals performing CEA. Conclusions—: This population-based study revealed a 63% decline in CEAs among asymptomatic patients between 2011 and 2017, possibly because of changing attitudes in the role of CEA. Reasons for the 25% decline in CEAs among symptomatic patients are unclear as UK guidelines on CEA have not changed for these patients. Whether the proportion of symptomatic patients with 50% to 99% ipsilateral stenosis has changed requires investigation. Abstract : Supplemental Digital Content is available in the text.